The physiology and pharmacology of singlet oxygen - Stief, Thomas W (Med Hypotheses, 2003)
Reactive oxygen species (ROS) are generated by many different cells. Singlet oxygen (1O2) and a reaction product of it, excited carbonyls (CO(*)), are important ROS. 1O2 and CO(*) are nonradicalic and emit light (one photon/molecule) when returning to ground state oxygen. Especially activated polymorphonuclear neutrophil granulocytes (PMN) produce large amounts of 1O2. Via activation of the respiratory burst (NADPH oxidase and myeloperoxidase) they synthesize hypochlorite (NaOCl) and chloramines (in particular N-chlorotaurine). Chloramines are selective and stable chemical generators of 1O2. In the human organism, 1O2 is both a signal and a weapon with therapeutic potency against very different pathogens, such as microbes, virus, cancer cells and thrombi. Chloramines at blood concentrations between 1 and 2 mmol/L inactivate lipid enveloped virus and chloramines at blood concentrations below 0.5 mmol/L, i.e. at oxidant concentrations that do not affect thrombocytes or hemostasis factors, act antithrombotically by activation of the physiologic PMN mediated fibrinolysis; this thrombolysis is of selective nature, i.e. it does not impair the hemostasis system of the patient allowing the antithrombotic treatment in patients where the current risky thrombolytic treatment is contraindicated. The action of 1O2 might be compared to the signaling and destroying gunfire of soldiers directed against bandits at night, resulting in an autorecruitment of the physiological inflammatory response. Chloramines (such as the mild and untoxic oxidant chloramine T(®) (N-chloro-p-toluene-sulfonamide)) and their signaling and destroying reaction product 1O2 might be promising new therapeutic agents against a multitude of up to now refractory diseases.